Effect of various anthelmintics on growing-finishing swine reared on dirt lots - Hines, Robert H.; Schoneweis, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials involving 262 pigs were conducted to evaluate five worming programs for growing-finishing pigs fed on dirt lots heavily infected with roundworm (Ascarid) eggs. The control pigs (no anthelmentic) were compared in performance (ADG, F/G) and lung liver lesions at slaughter with pigs that received ivermectin on day 1 or day 28, pyrantel tartrate for the first 28 days, or purge treatments between day 28 to 31 with dichlovos or fenbendazole. All pigs gained at a similar rate regard less of treatment; however, those pigs receiving fenbendozole were 8.4% more efficient and those receiving Ivermectin on day 28 were 6% more efficient when compared to the controls. Pigs receiving pyrantel tartrate, dichlorvos, and ivermectin on day 1 were similar to the control pigs in feed efficiency. Results for liver and lung lesion scores were varied. In trial 1, 12% of the Iivers were free of ascarid scars and 13.8% of the livers were ruled inedible. In trial 2, 23.3% of the livers showed no lesions, but a different U.S.D.A. inspector condemned 54.4% of the livers even though the average liver lesion scores were similar to those in trial 1.
Keywords: Swine; Growing-finishing pigs